2011
DOI: 10.1371/journal.pone.0018789
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for Side-Chain Polyglutamine Hydrogen Bonding in Irreversible Ataxin-3 Aggregation

Abstract: The protein ataxin-3 consists of an N-terminal globular Josephin domain (JD) and an unstructured C-terminal region containing a stretch of consecutive glutamines that triggers the neurodegenerative disorder spinocerebellar ataxia type 3, when it is expanded beyond a critical threshold. The disease results from misfolding and aggregation, although the pathway and structure of the aggregation intermediates are not fully understood. In order to provide insight into the mechanism of the process, we monitored the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 43 publications
10
70
0
Order By: Relevance
“…Previously published structural analyses of polyQ fibrils performed mostly on synthetic polyQ showed no similar structural transition (49 -51). However, one group reported differences in the FTIR spectra of fibrils from recombinant ataxin 3 containing 24 or 55 glutamines (52). The apparent discrepancy between results obtained using synthetic polyQ peptides and recombinant polyQ proteins highlights the importance of the natural context of polyQ stretches.…”
Section: Bs3-d0 Peptidesmentioning
confidence: 99%
“…Previously published structural analyses of polyQ fibrils performed mostly on synthetic polyQ showed no similar structural transition (49 -51). However, one group reported differences in the FTIR spectra of fibrils from recombinant ataxin 3 containing 24 or 55 glutamines (52). The apparent discrepancy between results obtained using synthetic polyQ peptides and recombinant polyQ proteins highlights the importance of the natural context of polyQ stretches.…”
Section: Bs3-d0 Peptidesmentioning
confidence: 99%
“…Peaks due to amino acid side chain can be observed in the protein mid-infrared absorption spectrum within a wide range. Interestingly, the analyses of these bands can give useful information on the amino acid side chain conformation, such as exposure and H-bonding (41). A review of amino acid side chain absorptions in the mid-infrared can be found in ref.…”
Section: Notesmentioning
confidence: 99%
“…These AT3 variants were expressed in E. coli strain BL21-CodonPlus (DE3)-RIL (E. coli B F− ompT hsdS (rB− mB−) dcm+ Tetr gal (DE3) endA Hte [argU ileY leuW Cam r ] (Stratagene, La Jolla, CA, USA) as GST-fusion proteins containing a PreScission Protease recognition site. The wild type AT3Q24 was cloned in a pQE30 vector (Qiagen Hamburg GmbH, Hamburg, Germany) and expressed as a His-tagged protein as previously described (Natalello et al, 2011). The variants AT3Q6 and AT3Q24-3UIM were obtained by PCR reactions using 5 -phosphorylated oligos and the construct pQE30/AT3Q24 as template.…”
Section: Cloning and Expression Of At3 Variantsmentioning
confidence: 99%
“…Protein content was determined using Coomassie brilliant blue G-250 (Thermo Fisher Scientific, Rockford, IL, USA) and BSA as a standard protein. To ensure that the protein variants under investigation were properly folded, they were routinely subjected to FT-IR analysis to assess secondary structure content (Natalello et al, 2011).…”
Section: Purification Of At3 Variantsmentioning
confidence: 99%